Outcome of Allogeneic Adult Stem Cell Therapy in Dogs Suffering from Osteoarthritis and Other Joint Defects. (28th June 2018) - Shah, Kiran; Drury, Tara; Roic, Ivelise; Hansen, Peter; Malin, Mark; Boyd, Richard; Sumer, Huseyin; Ferguson, Ray
Abstract : Osteoarthritis is a common condition that causes joint pain and stiffness that affects both humans and dogs. In Australia, allogeneic canine adipose-derived mesenchymal stem cells for therapy have been commercially available since 2010. In this report, we describe the outcome of the treatment of two hundred and three dogs diagnosed with degenerative arthritis with severe chronic pain in joints causing lameness at walk, reduced mobility, and functional disability. Posttreatment assessment data after 10 weeks revealed significant improvement (p < 0.007 ) of the symptoms: pain reduction, improvement of mobility, and increased daily activity as measured as quality of life score. Ninety percent of young dogs (<9 years) showed excellent improvement in pain and mobility and were able to run and resume normal activity. Sixty percent of older dogs showed good improvement. However, 12% of dogs did not exhibit any change in symptoms; one dog showed worsening of the symptoms. This report provides the support for the safety and efficacies of allogeneic adipose-derived mesenchymal stem cells in a regenerative therapeutic veterinary model.